Staphylococcus simulans bloodstream infection following CIED extraction. Issue 5 (27th May 2021) - Go, John Raymond; Corsini Campioli, Cristina; DeSimone, Daniel; Sohail, Muhammad Rizwan
Abstract : A 78-year-old man with an implantable cardioverter-defibrillator (ICD) presented with chills and malaise. His history was significant for heart failure with reduced ejection fraction and complete heart block. He had undergone permanent pacemaker placement that was later upgraded to an ICD 5 years before his presentation. Physical examination revealed an open wound with surrounding erythema overlying the device site. Blood cultures obtained on admission were negative. Transesophageal echocardiogram did not show valve or lead vegetations. He underwent a prolonged extraction procedure. Postoperatively, he developed septic shock and cultures from the device, and repeat peripheral blood cultures grew Staphylococcus simulans and Staphylococcus epidermidis . He was treated with intravenous vancomycin but had refractory hypotension, leading to multiorgan failure. He later expired after being transitioned to comfort care. The patient may have acquired S. simulans by feeding cows on a nearby farm, and the prolonged extraction procedure may have precipitated the bacteraemia.